2016
DOI: 10.3390/w8070273
|View full text |Cite
|
Sign up to set email alerts
|

Public Participation in Water Planning in the Ebro River Basin (Spain) and Tucson Basin (U.S., Arizona): Impact on Water Policy and Adaptive Capacity Building

Abstract: Abstract:The benefits of public participation in water management are recognized by governments, scholars, and stakeholders. These benefits, however, do not result from all engagement endeavors. This leads to the question: What are the determinants for effective public participation? Given a list of criteria for achieving the transformational capacity of participation, we analyze the benefits (including the influence on public policies) gained through public participation and the determinant factors for obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
0
17
0
3
Order By: Relevance
“…Furthermore, the high risk of flood poses a threat to both rural (agricultural) and urban areas. With five large cities lying within the river basin, floods in the area are not just disruptive but costly [31]. In terms of biodiversity, the pressures faced by the basin such as pollution, abstraction, morphological changes and other anthropogenic pressures all contribute towards negative impacts on the natural habitat and have an adverse effect on the quality of the living environment.…”
Section: Initial Explorationsmentioning
confidence: 99%
“…Furthermore, the high risk of flood poses a threat to both rural (agricultural) and urban areas. With five large cities lying within the river basin, floods in the area are not just disruptive but costly [31]. In terms of biodiversity, the pressures faced by the basin such as pollution, abstraction, morphological changes and other anthropogenic pressures all contribute towards negative impacts on the natural habitat and have an adverse effect on the quality of the living environment.…”
Section: Initial Explorationsmentioning
confidence: 99%
“…All governance actors across national, regional, and local levels are cooperating with the management committees to manage water resources based on the river basin system in Germany [68,69]. River basin authorities act as the main institutional body to govern water resources in each basin with cooperation of the central, regional, and local governments in Spain [13,70,71]. Based on the 1985 Water Law in Spain, river basin authorities are independent governance bodies with functional autonomy.…”
Section: Water-basin Managementmentioning
confidence: 99%
“…The needed system learning does not always emerge from collaboration processes: the quality of the process is important. In "Public Participation in Water Planning in the Ebro River Basin (Spain) and Tucson Basin (Arizona, USA): Impact on Water Policy and Adaptive Capacity Building", Ballester and Mott Lacroix compare case studies on the Ebro Basin in Spain and the Tucson Active Management Area in Arizona, USA, to determine the factors with significant influence on outcomes of participatory processes [11]. They found that while policy impacts depended largely on contextual factors, an increase in adaptive capacity was related to the quality of the participatory process.…”
Section: Tools For Building Water Management and Governance Capacitymentioning
confidence: 99%